Associations, témoignages, mythistoires - Georges Dertilis (L'Atelier du CRH)
In this article the author, a historian, describes the autobiography he published in 2013. This “micro-history” of his family, juxtaposed to the History of Greece since the eighteenth century, is studded with the incidents, which marked the author’s childhood during the Nazi occupation and the civil war, then his years of studying and teaching during and after the colonels’ dictatorship. In his article the author presents himself, ironically, as an historian trying in vain to exorcise his guilt for transgressing the rules of his discipline by writing a “mythistory”, whilst totally abandoned to the pleasures of a free, literary style. Having thus discovered that instead of doing history “il fait de la prose”, he goes on to a not so hackneyed conclusion: that autobiography is omnipresent in literature and the arts. He can thus evoke, in admiration, G. T. di Lampedusa who writes Il Gattopardo inspired by his family’s history, Luchino Visconti who obviously saw one of his ancestors in the person of Prince di Salina, and even Richard Strauss, whose “Letzte Lieder” resonate with their verses in a nostalgic, harmonious, serene testament